2012
DOI: 10.1002/cta.717
|View full text |Cite
|
Sign up to set email alerts
|

Łojasiewicz inequality and exponential convergence of the full‐range model of CNNs

Abstract: SUMMARYThis paper considers the full-range (FR) model of Cellular Neural Networks (CNNs) in the case where the signal range is delimited by an ideal hard-limiter nonlinearity with two vertical segments in the i −v characteristic. A ⁄ Lojasiewicz inequality around any equilibrium point, for a FRCNN with a symmetric interconnection matrix, is proved. It is also shown that the ⁄ Lojasiewicz exponent is equal to 1 2 . The main consequence is that any forward solution of a symmetric FRCNN has finite length and is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…We refer the reader to [27], and references therein, for an account of research results along this line. We refer the reader also to [22], [28], for other related results on convergence of FRCNNs with symmetric interconnections, and to [26] for an extended Lyapunov approach to study convergence of generalized gradienttype FRCNN models.…”
Section: Monotonicity Of Semiflowmentioning
confidence: 99%
“…We refer the reader to [27], and references therein, for an account of research results along this line. We refer the reader also to [22], [28], for other related results on convergence of FRCNNs with symmetric interconnections, and to [26] for an extended Lyapunov approach to study convergence of generalized gradienttype FRCNN models.…”
Section: Monotonicity Of Semiflowmentioning
confidence: 99%
“…However it is worth remarking that Theorem 7 is to the authors' knowledge the only existing result on convergence for nonsymmetric FR-CNNs with multiple EPs. Indeed, previous papers [22] and [45] have addressed convergence of FRCNNs with multiple EPs in the symmetric case by means of a Lyapunov approach, and an approach based on the principle of trajectories with finite length and the Lojasiewicz inequality, respectively. On the other hand, [46] and [47] have given conditions ensuring global asymptotic stability and global robust exponential stability of the unique EP for some classes of nonsymmetric FRCNNs with and without delays.…”
Section: B Cooperative Frcnnsmentioning
confidence: 99%
“…On one hand, it has been shown that there are relevant classes of FRCNNs displaying analogous convergence and stability properties as the corresponding SCNNs. These include: (1) FRCNNs with symmetric neuron interconnections, where convergence can be analyzed by means of a generalized Lyapunov approach based on an extended version of LaSalle's invariance principle , or by means of the principle of trajectories with finite length and the Łojasiewicz inequality ; (2) a general class of FRCNNs defined by gradient‐type systems ; (3) FRCNNs with nonsymmetric Lyapunov diagonally stable, or M‐matrices , for which it is possible to prove general results on global asymptotic stability. On the other hand, a counterexample by Corinto and Gilli has shown that there are classes of convergent nonsymmetric SCNNs for which the corresponding FRCNNs display non‐vanishing oscillations .…”
Section: Introductionmentioning
confidence: 99%